Filtered epithermal quasi-monoenergetic neutron beams at research reactor facilities. (March 2015) - Mansy, M.S.; Bashter, I.I.; El-Mesiry, M.S.; Habib, N.; Adib, M.
Abstract: Filtered neutron techniques were applied to produce quasi-monoenergetic neutron beams in the energy range of 1.5–133 keV at research reactors. A simulation study was performed to characterize the filter components and transmitted beam lines. The filtered beams were characterized in terms of the optimal thickness of the main and additive components. The filtered neutron beams had high purity and intensity, with low contamination from the accompanying thermal emission, fast neutrons and γ-rays. A computer code named "QMNB" was developed in the "MATLAB" programming language to perform the required calculations. Highlights: Quasi-monoenergetic neutron beams in energy range from (1.5–133) keV. Interference between the resonance and potential scattering amplitudes. Epithermal neutron beams used in BNCT.